The Influence of Islamic Work Ethics on Organizational Commitment in Halal Cosmetic Industry: Does Job Satisfaction Matter? - Firmansah, Yayan; Sari, Dilla Novita (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
This study investigates the influence of Islamic work ethics on organizational commitment, with job satisfaction as a moderating variable. Using a quantitative approach, data were collected from 171 employees through questionnaires and analyzed with regression and moderation tests. The results show that Islamic work ethics positively and significantly affect organizational commitment, while job satisfaction does not act as a significant moderator. The study highlights the relevance of Islamic work ethics in enhancing employee commitment, offering insights into its application in the halal cosmetics industry. Organizations are recommended to uphold these ethical values to foster workplace harmony and productivity.